Colonic Polypoid Arteriovenous Malformation Causing Symptomatic Anemia. Issue 10 (October 2019) - Rzepczynski, Allison; Kramer, Jason; Jakate, Shriram; Cheng, Lin; Singh, Ajaypal
Abstract : ABSTRACT: Vascular ectasias, which can be classified as angiodysplasias and arteriovenous malformations (AVMs), accounts for approximately 3% of lower gastrointestinal bleeding. Typically, colonic AVMs are solitary, large, and flat or elevated red lesions on endoscopy. We present an interesting case of a polypoid ulcerated AVM in the transverse colon causing symptomatic anemia, which was resected endoscopically with a resolution of symptoms. Polypoid colonic AVMs are rather rare with only 15 other cases described in the literature. This case highlights the approach to endoscopic management of these lesions.